Tratamento de águas cinza geradas em edificação unifamiliar de médio porte, visando ao seu reuso - Oliveira, Taísa Machado de (2014)
Wastewater reuse has emerged as element in the management of water demand. The supply and conservation of drinking water quality as well as the potential decrease of water resources pollution are some of the reasons of such increasing relevance. Domestic reuse is an attractive option due to relatively high water consumption for a demanding population. In this context, greywater is on the spotlight; the urban effluent constituted by wash-water free of flush toilets contributions. The separation process using membrane is one of the available technologies to treat effluents. However, the performance of these membranes is restrained by particles and organic compounds deposited and accumulated on the membrane surface; they generate encrustations and decrease the permeate flow during the operation and deteriorate the permeate quality; consequently the membrane viability is reduced. According to this approach, the objective of this study was to assess the viability of greywater treatment through separation process using membrane (submerged micro-infiltration and reverse osmosis) seeking good-quality water that allows reuse for ends other than consumption in single-family houses. For this purpose, we conducted greywater characterization. They present significant variations regarding physical, chemical and bacteriological quality because of factors such as the source generating the effluent, family habits and chemical products used in domestic environments (detergent, soap, shampoo). We also observed high concentrations of apparent color, turbidity, suspended and dissolved solids, anionic surfactants, organic matters and fecal coliforms. Using a scale workbench, we studied four modules of hollow-fiber membrane with micro-infiltration of 0.4μm pores and different packing densities. We assessed the most satisfactory operation conditions (pressure and aeration), the permeate flow behavior for 100 minutes, the effect of encrustations on modules, the efficiency in removing physical, chemical and biological parameters, and finally, the permeate quality. Therefore, we applied the most satisfactory results in the real-scale treatment. At the final stage of each experiment, we carried out the physical cleaning/backwash, which was efficient to recover the permeate flow and the membrane hydraulic permeability. Finally, we installed a unit of semi-pilot greywater treatment in a single-family house consisting of the coupling of the modules of submerged micro-infiltration of hollow-fiber as well as flat reverse osmosis and spiral reverse osmosis. Modules performance and effluent quality were then assed. The physical process of separation membranes MF and OI rejição allowed over 97% of the physical parameters. The average apparent color was found to be 3 ± 2 UNITS PtCo APHA, turbidity, 2 ± 1 FAU and absence of suspended solids. The mean amount of organic matter determined in terms of COD and BOD5 was 28.3 ± 9.5 mg L-1 and 4 ± 2 mg L-1 and rejecting 91.1±4.7 % to 98 ± 1 %, respectively. This ensured the water quality within the norms of domestic reuse. Results revealed that the separation process using membrane is technically viable alternative to treat greywater. The final effluent quality emphasized the possibility of reusing domestic sewage for ends other than consumption, such as discharge of flush toilets, garden irrigation, car, pavement among others. Such reuse could lead to alterations in the global management of water resources and a consequent sustainable scenario.